A study on using storytelling to improve English speaking for students at a primary school in Hanoi - Phạm, Thị Hân (2020)
This research aims to investigate the effectiveness of storytelling on speaking skill and their attitudes to this technique in speaking at Ly Nam De Primary School. This aim is specified into the following objectives: 1. To examine the impact of applying storytelling in teaching speaking for the young learners at a primary school in Hanoi. 2. To determine the students’ attitudes in learning speaking through storytelling